Recent Advances in Vertical Alveolar Bone Augmentation Using Additive Manufacturing Technologies - Vaquette, Cedryck; Mitchell, Joshua; Ivanovski, Sašo (Frontiers in Bioengineering and Biotechnology, 2022)
Vertical bone augmentation is aimed at regenerating bone extraskeletally (outside the skeletal envelope) in order to increase bone height. It is generally required in the case of moderate to severe atrophy of bone in the oral cavity due to tooth loss, trauma or surgical resection. Currently utilized surgical techniques, such as autologous bone grafts, distraction osteogenesis and Guided Bone Regeneration (GBR), have various limitations, including morbidity, compromised dimensional stability due to suboptimal resorption rates, poor structural integrity, challenging handling properties and/or high failure rates. Additive manufacturing (3D printing) facilitates the creation of highly porous, interconnected 3-dimensional scaffolds that promote vascularization and subsequent osteogenesis, while providing excellent handling and space maintaining properties. This review describes and critically assesses the recent progress in additive manufacturing technologies for scaffold fabrication directed at vertical bone augmentation and their in vivo application.